Comparison of Mechanical Properties of Normal and Fibre Reinforced Concrete (Grade M15) - Bista, Sagar; Airee, Sagar; Dhital, Shikshya; Poudel, Srijan; Neupane, Sujan (Journal of Advanced College of Engineering and Management, 2019)
Concrete is weak in tension, hence some measures must be adopted to overcome this deficiency as well as to enhance physical and other mechanical properties but in more convenient and economical method. Through many research from the past, it has been observed that addition of different types of fibres has been more effective for this purpose. This report presents the work undertaken to study the effect of steel and hay fibre on normal cement concrete of M-15 Grade on the basis of its mechanical properties which include compressive and tensile strength test and slump test as well. Although hay fibres are abundantly available in Nepal, no research have been popularly conducted here regarding the use of hay fibres in concrete and the changes brought by it on concrete’s mechanical properties. Experiments were conducted on concrete cubes and cylinders of standard sizes with addition of various percentages of steel and hay fibres i.e. 0.5%, 1% and 1.5% by weight of cement and results were compared with those of normal cement concrete of M-15 Grade. For each percentage of steel and hay fibre added in concrete, six cubes and six cylinders were tested for their respective mechanical properties at curing periods of 14 and 28 days. The results obtained show us that the optimum content of fibre to be added to M-15 grade of concrete is 0.5% steel fibre for compression and 0.5% hay fibre content for tension by weight of cement. Also, addition of steel and hay fibres enhanced the binding properties, micro cracking control and imparted ductility.In addition to this, two residential buildings were modeled in SAP software, one with normal concrete and other with concrete containing 0.5% steel fibre. Difference in reinforcement requirements in each building was computed from SAP analysis and it was found that 489.736 Kg of reinforcement could be substituted by 158.036 kg of steel fibres and decrease in materials cost of building with 0.5% steel fibre reinforced concrete was found to be Rs. 32,100.